PELATIHAN MEMBUAT KONTEN PEMBELAJARAN DALAM PENINGKATAN KUALITAS KOMPETENSI GURU DAN HASIL BELAJAR PESERTA DIDIK SMP NEGERI 1 SUKAWATI - Ida Ayu Agung Ekasriadi; Putu Dessy Fridayanthi; I Komang Sukendra; Gusti Ayu Made Puspawati (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2025)
This community service activity aims to provide a solution to the problem of lack of understanding and skills of teachers in designing interesting and relevant digital learning content, in order to improve teacher professional competence and student learning outcomes at SMP Negeri 1 Sukawati. The implementation of the activity is carried out through two main stages, namely training and mentoring. In the training stage, teachers are given a conceptual understanding and practical skills in using various digital applications such as Canva, CapCut, and Powtoon to create interactive learning media. The next stage is technical mentoring which is carried out periodically to ensure that teachers are able to implement the training results in the learning process in the classroom. The results of the activity show a significant increase in teacher competence in creating digital learning content and the formation of several learning video products as real outputs of the training. In addition, this activity encourages the integration of digital content in the Merdeka Curriculum in a more systematic and sustainable manner. Thus, this community service activity has a real positive impact in supporting technology-based educational transformation in the school environment.